Tactical swimming activity and heart rate aspects of youth water polo game - Lupo, C.; Capranica, L.; Cugliari, G.; Gomez, M. A.; Tessitore, A. (The Journal of Sports Medicine and Physical Fitness, 2016)
BACKGROUND: